Bencana Hutan dalam Hubungan Internasional - Loade Muhamad Fathun (Andalas Journal of International Studies (AJIS), 2016)
This article will answer the question why Indonesia is not yet fullyoptimized in solving forest fires. The types of literature is qualitative analysis techniques with collecting secondary data (library research). In result that the forest fires in Indonesia is because inability of the government to preserve forest, or other terms are neglected phenomenon. It still repeated every year with 20 trillion losses in 2015 with total land area about 2.1 million hectares. This condition is equal to four timesBali island and 32 times the size of Jakarta. Analysis process that still recurrence of catastrophic forest fires, as the result by not optimal factors: a) governance management of the disaster, b) Not optimal in disaster as an instrument of diplomacy, it relates to how Indonesia influence a number of countries to help tackle the fire, c) the consequences and legal compliance related to transboundary haze. Smoke pollution control is not legally ratified by Indonesia, posed no legalconsequences for Indonesia. Contrary to the Geneva Convention, the Riodeclaration and the declaration Stockholm advocated that the country should maintain its natural and conformity with nature, so it does not interfere with the activities of other countries. Keyword: Disaster, Diplomacy, Compliance Theory, Rational Choice